PENGARUH KOMPETENSI TUTOR TERHADAP KINERJA PEMBELAJARAN DI PUSAT KEGIATAN BELAJAR MASYARAKAT KABUPATEN SIJUNJUNG - Roni Indra Partini; Suharno; Lusiana; Silvia Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of tutor competence on learning performance at the Community Learning Activity Center (PKBM) in Sijunjung Regency. Tutor competence, as non-formal educators, plays a crucial role in the success of the learning process. This study used a quantitative approach with a survey method. The sample consisted of 100 tutors from 15 PKBMs, selected purposively. Data were collected through questionnaires and analyzed using simple linear regression. The results showed that tutor competence significantly influenced learning performance, with a coefficient of determination (R²) of 0.62. This finding confirms that improving tutor competence can directly improve the quality of learning in PKBM.